Percutaneous Pulmonary Valve Implantation Alters Electrophysiologic Substrate. Issue 10 (30th September 2016) - Nguyen, Hoang H.; Shahanavaz, Shabana; Van Hare, George F.; Balzer, David T.; Nicolas, Ramzi; Avari Silva, Jennifer N.
Abstract : Background: Percutaneous pulmonary valve implantation (PPVI) is first‐line therapy for some congenital heart disease patients with right ventricular outflow tract dysfunction. The hemodynamics improvements after PPVI are well documented, but little is known about its effects on the electrophysiologic substrate. The objective of this study is to assess the short‐ and medium‐term electrophysiologic substrate changes and elucidate postprocedure arrhythmias. Methods and Results: A retrospective chart review of patients undergoing PPVI from May 2010 to April 2015 was performed. A total of 106 patients underwent PPVI; most commonly these patients had tetralogy of Fallot (n=59, 55%) and pulmonary insufficiency (n=60, 57%). The median follow‐up time was 28 months (7‐63 months). Pre‐PPVI, 25 patients (24%) had documented arrhythmias: nonsustained ventricular tachycardia (NSVT) (n=9, 8%), frequent premature ventricular contractions (PVCs) (n=6, 6%), and atrial fibrillation/flutter (AF/AFL) (n=10, 9%). Post‐PPVI, arrhythmias resolved in 4 patients who had NSVT (44%) and 5 patients who had PVCs (83%). New arrhythmias were seen in 16 patients (15%): 7 NSVT, 8 PVCs, and 1 AF/AFL. There was resolution at medium‐term follow‐up in 6 (86%) patients with new‐onset NSVT and 7 (88%) patients with new‐onset PVCs. There was no difference in QRS duration pre‐PPVI, post‐PPVI, and at medium‐term follow‐up ( P =0.6). The median corrected QT lengthened immediately post‐PPVI but shortened significantly at midterm follow‐up ( P <0.01). Conclusions: PPVI reduced the prevalence of NSVT. The majority of postimplant arrhythmias resolve by 6 months of follow‐up.